Peningkatan kemampuan pemahaman konsep zat tunggal dan campuran melalui model pembelajaran kooperatif tipe two stay two stray pada peserta didik kelas v sekolah dasar - Agus Gumelar; Rukayah Rukayah; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2021)
Abstract.This research aimed to increase the ability to understanding the concept of single and mixed subtance by applying Two Stay Two Stray learning model to all The V grade students of elementary school III Slogohimo Year 2018/2019. The subject of this research is the teacher and the V grade students ofSlogohimo Elementary School Year 2018/2019 which was there 32 students.The technique of data validity was used source and technique triangulation. The result of the data in this research showing that the ability to understand singgle and mixed subtance concept was intereased in each cycles. Preaction show the data 6,35%, in the cycles I show the data clasical completeness result from te class 46,9%, and then 90,6% in cycles II. Based on the description above we can conclude that the applying of Two Stay Two Stray learning model can increase the ability of V grade student III Slogohimo Elementary School Year 2018/2019 to understand the single and mixed subtance concept.Keyword :Two Stay Two Stray, The concept understanding, single and mixed subtance